2021
DOI: 10.1080/23311975.2021.1962487
|View full text |Cite
|
Sign up to set email alerts
|

Does absorptive capacity moderate the relationship between entrepreneurial orientation and supply chain resilience?

Abstract: Supply chain resilience (SCR) is often seen as a dynamic capability that enables firms to effectively cope with disruptions and unforeseen events in the business environment. However, empirical research focusing on influencing factors on SCR is still limited. Based on the resource-based view (RBV) and the dynamic capabilities theory (DCT), we examine if absorptive capacity (AC) does in fact moderate the relationship between entrepreneurial orientation (EO) and SCR. Drawing upon a sample of 171 Yemeni manufactu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 94 publications
(122 reference statements)
1
17
0
Order By: Relevance
“…Indeed, in light of the previous studies, we conclude that entrepreneurial innovation develops a positive relationship between packaging and labeling strategies and consumer buying intention ( 47 ). Consistently, the study findings revealed, absorptive capacity positively moderates the relationship between entrepreneurial innovation and consumer purchasing behavior, which is also consistent with the previous literature ( 20 ). Indeed, based on the study analysis, all the hypotheses are significantly supported and accepted.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Indeed, in light of the previous studies, we conclude that entrepreneurial innovation develops a positive relationship between packaging and labeling strategies and consumer buying intention ( 47 ). Consistently, the study findings revealed, absorptive capacity positively moderates the relationship between entrepreneurial innovation and consumer purchasing behavior, which is also consistent with the previous literature ( 20 ). Indeed, based on the study analysis, all the hypotheses are significantly supported and accepted.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, the dynamic capability enables the companies to implement the EI practices (61), allowing the consumers to make informed decisions. Moreover, the literature demonstrates that absorptive capacity positively links entrepreneurial innovation capabilities (20), making the organization realize the need for changing consumer behavior (62). Perhaps, absorptive capacity strengthens the dynamics of the information society (63), making the entrepreneurial technological innovation enhance consumer buying behavior.…”
Section: Moderating Role Of Absorptive Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…From the discussion, it is clear that the existing literature shows little attention to how SMEs manage green innovation (Singh et al, 2021). Needless to say, SMEs should possess relevant entrepreneurial skills (Al‐Hakimi & Borade, 2020; Goaill & Al‐Hakimi, 2021), be connected to external networks (Al‐Hakimi et al, 2022), and receive government assistance to grow (Veronica et al, 2020). However, there is a dearth of literature to provide guidance on how to proceed.…”
Section: Introductionmentioning
confidence: 99%
“…The firms surveyed are the SMEs located in Yemen whose contribution to the country's GDP is negligible despite their dominance in the manufacturing sector (AlQershi et al , 2020; Al-Hattami et al , 2021; Goaill and Al-Hakimi, 2021). A major issue for their poor performance is the SC disruptions resulting from the conflict and political crisis in the country, including close inspections at seaports that have restricted imports, delayed arrival of raw materials as well as high insurance and shipping costs (Morris et al , 2019; Tandon and Vishwanath, 2020).…”
Section: Introductionmentioning
confidence: 99%